2016
DOI: 10.1097/phh.0000000000000359
|View full text |Cite
|
Sign up to set email alerts
|

Minigrants for Community Health

Abstract: Even with very small amounts of money, minigrants show promise as an ethical, inexpensive, empowering, and effective health promotion strategy to enable families and communities to improve their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Extant literature highlights the wide range of public health initiatives supported by mini-grants, including physical activity [39], healthy eating [5, 7, 8, 10], childhood wellbeing [11], and other objectives outlined in Healthy People 2020 [1, 12]. For such public health initiatives, mini-grant funding varies substantially per funded project, from as low as $40 to as much as $50,000 [7]. Early evaluations of this approach focused, necessarily, on “process,” specifically the organizational administrative processes and partnerships needed to successfully administer the funding and implement the community-based activities [1, 3, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Extant literature highlights the wide range of public health initiatives supported by mini-grants, including physical activity [39], healthy eating [5, 7, 8, 10], childhood wellbeing [11], and other objectives outlined in Healthy People 2020 [1, 12]. For such public health initiatives, mini-grant funding varies substantially per funded project, from as low as $40 to as much as $50,000 [7]. Early evaluations of this approach focused, necessarily, on “process,” specifically the organizational administrative processes and partnerships needed to successfully administer the funding and implement the community-based activities [1, 3, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the community gardening spaces that ENYF, WCP, and FLV have cultivated offer the space, soil and, especially with FLV in Laramie, affordable water, that are all necessary for gardening but not everyone has access to. Results from another study within the Food Dignity project, where US$40 gardening mini-grants were randomly provided to half the attendees at a gardening workshop, found that even small amounts of material support spurred interested people to start or expand food gardens (Porter, McCrackin, & Naschold, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The methods conventionally accepted as rigorous are beyond the scope of this paper and are detailed in our theses, dissertations, and other publications (Armstrong, 2015;Arthur, 2015;Bradley, 2011Bradley, , 2015Gregory, 2017;Gregory & Peters, this issue;Meek et al, 2017;Porter, 2010Porter, , 2013Porter, McCracken, & Naschold, 2016). However we also engaged in emotionally rigorous work, which we describe in the next section.…”
Section: Building Bridgesmentioning
confidence: 99%